Preference for basic IgG in early syphilis. Issue 3 (June 1975) - Van Der Sluis, J J; Menke, H E; Neumann, H
Abstract : By differential IgG measurements of sera of 27 patients with early infectious syphilis, it was found that infection with T. pallidium results in a preferential synthesis of IgG immunoglobulins characterized by high isoelectric points. The decrease in total IgG level observed after 6 weeks of treatment can to a large extent be accounted for by the decrease in basic IgG concentration. The relationship between the total and basic IgG levels and the number of T. pallidum present in the body during the three early stages of the disease studied is discussed.